2021
DOI: 10.3390/metabo11110760
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria-Lowering Effects of Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors in Chronic Kidney Disease Patients: A Real-World Multicentric Study

Abstract: Control of dyslipidemia in chronic kidney disease (CKD) is not always guaranteed with statins and/or ezetimibe. Proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) have opened up a new era in lipid control, but their effect on renal function and proteinuria in real life have not yet been evaluated. The aim of the present study was to analyze the evolution of renal function and proteinuria in a cohort of CKD patients treated with PCSK9i. This retrospective multicentric cohort study included CKD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It might be postulated that in patients with pronounced proteinuria, PCSK9 might not only be involved in the development of hyperlipidemia but might also be correlated with kidney damage (28)—whether causally or as a consequence requires further data. Interestingly, a recent study in patients with CKD receiving PCSK9 inhibitors observed not only an LDL cholesterol reduction of 51% but also an improvement of proteinuria during 1 year of follow-up (29).…”
Section: Discussionmentioning
confidence: 99%
“…It might be postulated that in patients with pronounced proteinuria, PCSK9 might not only be involved in the development of hyperlipidemia but might also be correlated with kidney damage (28)—whether causally or as a consequence requires further data. Interestingly, a recent study in patients with CKD receiving PCSK9 inhibitors observed not only an LDL cholesterol reduction of 51% but also an improvement of proteinuria during 1 year of follow-up (29).…”
Section: Discussionmentioning
confidence: 99%